2016
DOI: 10.1111/jocn.13191
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies and challenges in peritoneal dialysis: a qualitative study of renal nurses’ experiences

Abstract: Still psychomotor skills dominate peritoneal dialysis patient training, there is a need of both a deeper understanding of affective learning objectives and the accurate use of (self-)assessment tools, particularly for health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
4
14
0
10
Order By: Relevance
“…Effective communication can, however, be a challenging task for PD nurses. Bergjan and Schaepe () have described how some nurses were unaware that their communication style used during teaching was having a negative impact on their patients. In another study, when nurses used more open‐ended questions, explored topics brought up by patients, and refrained from using commands or reprimands, patient satisfaction improved as well (Boscart ).…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication can, however, be a challenging task for PD nurses. Bergjan and Schaepe () have described how some nurses were unaware that their communication style used during teaching was having a negative impact on their patients. In another study, when nurses used more open‐ended questions, explored topics brought up by patients, and refrained from using commands or reprimands, patient satisfaction improved as well (Boscart ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has showed that timely and adequate patient education can balance modality selection [ 43 , 44 ], prepare for a better initiation of dialysis [ 45 ], and promote independence, while also encouraging self-management [ 46 , 47 ]. Recent advances in CKD patient education recommend the development of training programs based on the principles of the adult learning theory, which initially assesses individuals’ ability and willingness to learn [ 48 , 49 ]. Demonstration and instruction are the most widely used teaching activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, if different trainers are involved in the training process and each of them demonstrates things differently, this results in the patients becoming confused. In addition, instructions and demonstrations should be simple and concise [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the related training is necessary for controlling peritonitis. [ 5 ] Educating these patients is difficult due to such barriers as cognitive impairment because of advanced uremia,[ 5 ] memory loss,[ 6 ] physical disorders caused by chronic fatigue, loss of physical strength, and lack of energy,[ 7 ] old age, different-related diseases, and lack of motivation. [ 5 ] Psychological problems related to the loss of confidence and the feeling of dependence on technology for survival make the patient worry, and this stress aggravates the problems in learning.…”
Section: Introductionmentioning
confidence: 99%